2015
DOI: 10.1128/aem.02296-15
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Immunity and Community Structure of a Multiple-Strain Pathogen in the Tick Vector

Abstract: bMany vector-borne pathogens consist of multiple strains that circulate in both the vertebrate host and the arthropod vector. Characterization of the community of pathogen strains in the arthropod vector is therefore important for understanding the epidemiology of mixed vector-borne infections. Borrelia afzelii and B. garinii are two species of tick-borne bacteria that cause Lyme disease in humans. These two sympatric pathogens use the same tick, Ixodes ricinus, but are adapted to different classes of vertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
85
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(94 citation statements)
references
References 98 publications
6
85
3
Order By: Relevance
“…This gene codes for outer surface protein C (OspC), which is a critical virulence factor for the infection of the vertebrate host (45,46). The ospC alleles can be clustered into ospC major groups (oMGs), which are more than 8% divergent in DNA sequence from other such clusters (5,24,(42)(43)(44). We have previously shown that genetic divergence among sequences belonging to the same oMG is Ͻ2% and that there are no intermediately divergent (2 to 8%) ospC sequences (24).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This gene codes for outer surface protein C (OspC), which is a critical virulence factor for the infection of the vertebrate host (45,46). The ospC alleles can be clustered into ospC major groups (oMGs), which are more than 8% divergent in DNA sequence from other such clusters (5,24,(42)(43)(44). We have previously shown that genetic divergence among sequences belonging to the same oMG is Ͻ2% and that there are no intermediately divergent (2 to 8%) ospC sequences (24).…”
mentioning
confidence: 99%
“…However, field studies that characterize the patterns of cooccurrence and abundance of multiplestrain vector-borne pathogens in the arthropod vector can indicate which pathogen strains are likely to have negative (or positive) interactions with each other in nature. Such field studies have made significant contributions to our understanding of these important infectious diseases (23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
See 3 more Smart Citations